Faktor Kondisi dan Pola Pertumbuhan Oxygaster anomalura - Maslimah Hasibuan; Rusdi Machrizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to obtain information related to the biological and ecological aspects of the Oxygaster anomalura in the Mailil River, Bandar Kumbul Village. The method used in this research is exploratory. Sampling was done using a fishing rod. The growth pattern was calculated using the length-weight relationship using the Linear Allometric Model (LAM), while the condition factor used the Fulton formula (K) and relative weight (Wr). The results showed that as many as 30 samples of Sulum Fish (Oxygaster anomalura) were caught during the study. Analysis of the length-weight relationship showed a negative allometric relationship with a value of b=1.94 (b>3). The Fulton condition factor (K) value is 1,195, while the value of the relative condition factor (Wr) is 169.42. In conclusion, the Mailil River as an ecosystem and habitat for O. anomalura fish is balanced. Keywords: Condition Factor, Oxygaster anomalura, Mailil River